Предмет: Алгебра, автор: Аноним

Помогите пожалуйста!!
Упростите выражение:
1)(х-2)(х-11)-2х(4-3х)
2)(а+6)(а-3)+(а-4)(а+5)
3)(у-8)(2у-1)-(3у+1)(5у-2)

Ответы

Автор ответа: Отличница1234567
0
1)(x-2)(x-11)-2x(4-3x)=x2-11x-2x+22-8x+6x2=7x2-22x+22
2)(a+6)(a-3)+(a-4)(a+5)=a2-3a+6a-18+a2+5a-4a-20=2a2+4a-38
3)(y-8)(2y-1)-(3y+1)(5y-2)=2y2-y-16y+8-15y2+6y-5y+2=-17y2-16y+10
Автор ответа: Аноним
0
Спасибо)))
Автор ответа: Отличница1234567
0
Всегда пожалуйста.
Автор ответа: selmash21
0
1)=х^2-11х-2х+22-8х+6х^2=7х^2-21х+22

2)=а^2-3а+6а-18+а^2+5а-4а-20=2а^2+4а-38

3)=2у^2-у-16у+8-15у^2+6у-5у+2=-13у^2-16у+10
Автор ответа: Аноним
0
Спасибо)
Похожие вопросы